An ultra-high performance geopolymer concrete suitable for rapid repair of heavy railway track and bridge and a preparation method thereof

CN123003196APending Publication Date: 2026-10-30SHIJIAZHUANG TIEDAO UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611132802.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]CN108892424A中的PVA纤维与纳米SiO2主要作为独立增强组分加入,该技术未公开改性PVA纤维与钢纤维按特定比例复配的复合纤维体系,也未针对重载铁路轨道与桥梁快速修复场景下的早期强度、施工流动性保持、界面斜剪粘结性能和低收缩性能进行协同优化

Benefits of technology

[0033]1、本发明以矿渣粉和硅灰作为主要胶凝材料,通过碱激发形成地聚物胶凝体系,减少水泥熟料用量,实现工业副产物的资源化利用,具有绿色低碳和二次利用价值。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of ultra-high performance geopolymer concrete suitable for heavy load railway track and bridge rapid repair and preparation method thereof, belong to building material technical field.Concrete includes matrix material and composite fiber;Matrix material includes slag powder 1 portion, silica fume 0.26-0.34 portion, medium sand 1.05-1.25 portion, alkali activator solution 0.28-0.38 portion, modified water reducing agent 0.012-0.030 portion and water 0.06-0.10 portion by slag powder 1 weight portion;Composite fiber is composed of modified PVA fiber and steel fiber, and composite fiber is added in total volume of ultra-high performance geopolymer concrete mixture, and the total volume of composite fiber is 1.5% to 2.0%;When preparing, after mixing slag powder and silica fume, alkali activator solution, water, modified water reducing agent, medium sand and composite fiber are added in turn, stirring and shaping and curing.The material obtained by the application has the characteristics of high early strength, good toughness, excellent interfacial bonding performance, low drying shrinkage and green low carbon, and is suitable for heavy load railway track and bridge rapid repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, and in particular to a method for preparing ultra-high performance geopolymer concrete suitable for rapid repair of heavy-load railway tracks and bridges. The prepared material possesses excellent mechanical properties and high toughness, and utilizes industrial by-products and an environmentally friendly formula, making it a green and low-carbon new type of building material. Background Technology

[0002] Heavy-haul railways, with their track and bridge structures subjected to high axle loads, high-frequency train loads, and environmental erosion during long-term service, are prone to cracking, fragmentation, wear, and interface delamination in track components (such as track slabs, ballast beds, fastener areas, and sleeper supports). Bridge structures (such as bridge decks, beam ends, bearing pads, pier surfaces, and the interface between new and old concrete) also frequently suffer from cracking, spalling, localized crushing, and interface loosening. These damages may be exacerbated under earthquakes or severe weather conditions. Repair materials need to possess good early strength, workability, interfacial bonding properties, and crack toughness to meet the requirements of emergency repairs and rapid restoration of structural functionality. Traditional silicate cement-based repair materials suffer from slow hardening, insufficient early strength, high risk of shrinkage cracking, and insufficient ability to coordinate deformation with the old concrete interface. While ultra-high performance concrete (UHVPC) boasts high strength and durability, its large clinker consumption leads to significant carbon emissions and autogenous shrinkage issues. Geopolymer concrete, using industrial byproducts such as slag powder and silica fume as primary cementing materials, forms a cementing system through alkali-activated reactions, offering advantages such as rapid early strength development, good durability, and low carbon footprint. However, slag-based polymer systems have a rapid reaction rate and a short construction window. Furthermore, the UHVPC matrix is ​​brittle, and matrix strength alone is insufficient to meet the comprehensive requirements of crack toughness, interfacial bonding, and fatigue damage resistance in the repair layer. Fiber reinforcement is a crucial means of improving the toughness and crack resistance of high-strength repair materials. Steel fibers possess high tensile strength and elastic modulus, making them suitable for macroscopic crack bridging and post-cracking load bearing; PVA fibers, with their smaller diameter and greater quantity, are suitable for micro-crack control and early shrinkage crack suppression. However, ordinary PVA fibers have a strong hydrophilic surface, which easily forms strong chemical bonds in inorganic cementitious matrices. During crack propagation, this may lead to premature fiber breakage rather than stable slippage and energy consumption during pull-out. Therefore, it is necessary to regulate the PVA fiber interface and form a multi-scale composite toughening system with steel fibers to balance the early strength, workability, interfacial adhesion, crack toughness, and volume stability of the rapid repair material.

[0003] In the prior art, CN108892424A discloses a nano-SiO2 and PVA fiber reinforced geopolymer mortar. This technology improves the flexural strength, toughness and crack control performance of the material by adding PVA fiber and nano-SiO2 to the geopolymer mortar system.

[0004] CN106380147B discloses a high-temperature resistant and high-ductility fiber-reinforced cementitious composite material and its preparation method. The material is based on a cementitious system, and the reinforcing fibers include at least basalt fibers to improve the high-temperature resistance and ductility of the material.

[0005] In CN108892424A, PVA fibers and nano-SiO2 are mainly added as independent reinforcing components. This technology does not disclose a composite fiber system in which modified PVA fibers and steel fibers are compounded in a specific ratio, nor does it perform synergistic optimization on early strength, construction fluidity retention, interfacial shear bond performance, and low shrinkage performance in the context of rapid repair of heavy-haul railway tracks and bridges. CN106380147B's technology mainly targets cement-based composite material systems, not slag-silica fume high-alkali geopolymer systems. Therefore, existing technologies still cannot simultaneously solve the problem of balancing early strength development, construction operability, interfacial bond performance, crack resistance, and low shrinkage performance in rapid repair materials for heavy-haul railway tracks and bridges. There is an urgent need for an ultra-high performance geopolymer concrete suitable for rapid repair of heavy-haul railway tracks and bridges and its preparation method. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides an ultra-high performance geopolymer concrete suitable for rapid repair of heavy-load railway tracks and bridges, and its preparation method. This material, by controlling the proportions of slag powder, silica fume, graded fine sand, alkali activator solution, added water, and modified water-reducing agent, and employing a composite fiber system composed of modified PVA fibers and steel fibers, achieves a combination of excellent workability, early strength, interfacial bonding, crack resistance, and low shrinkage.

[0007] Specifically, the matrix material, based on 1 part by weight of slag powder, consists of the following raw materials in parts by weight: 1 part slag powder; 0.26-0.34 parts silica fume; 1.05-1.25 parts medium sand; 0.28-0.38 parts alkali activator solution; 0.012-0.030 parts modified water-reducing agent; and 0.06-0.10 parts water. The composite fiber is composed of modified PVA fiber and steel fiber. Based on the total volume of the ultra-high performance geopolymer concrete mixture, the total volume content of the composite fiber is 1.5%-2.0%, of which the volume content of modified PVA fiber is 0.3%-0.5%, and the volume content of steel fiber is 1.2%-1.5%.

[0008] Furthermore, the slag powder is S95 grade blast furnace slag powder with a specific surface area of ​​420-450 m². 2 / kg, density is 2.8~3.0g / cm³ 3 The CaO content is 38%–42%, and the SiO2 content is 32%–36%.

[0009] The silica fume has a SiO2 content ≥92%, an average particle size of 0.1–0.5 μm, and a specific surface area of ​​18000–22000 m². 2 / kg, water requirement ratio ≤105%;

[0010] The medium sand is natural river sand that has been screened, with a fineness modulus of 2.6 to 2.8, a mud content of <1.0%, a mud lump content of <0.5%, and a moisture content of <0.1%.

[0011] Furthermore, the alkaline activator solution is prepared by the following steps:

[0012] Add 20-30g of sodium hydroxide to 50mL of pure water in three batches while stirring. Stir at 400r / min until the sodium hydroxide is completely dissolved. Let it stand and cool to 25℃. Then pour in 150-160g of liquid sodium silicate (modulus 3.32, solid content 39.99%) and stir at 400r / min for 20-30min until the solution is transparent and homogeneous. After that, let it stand at room temperature for 24h to obtain the alkali activator solution.

[0013] Furthermore, the modified water-reducing agent comprises the following raw materials in parts by weight: aliphatic water-reducing agent: 25-30 parts; hydroxypropyl methylcellulose: 2-3 parts; retarder: 4-5 parts.

[0014] Furthermore, the aliphatic water-reducing agent is prepared by the following steps:

[0015] Step A1: Add 200 mL of pure water to the reactor, then add 8.0–10.0 g of sodium sulfite (AR; purity 97%) to the pure water while stirring. Heat the reactor to 50–60 °C and stir at a constant temperature until the solid components are completely dissolved.

[0016] Step A2: Add 20.0-22.0g of cyclohexanone (AR; purity 99.5%) to the reactor and continue to stir and sulfonate at a constant temperature of 45-55℃ for 50-60min.

[0017] Step A3: After sulfonation, add 90-110 mL of formaldehyde solution with a mass fraction of 35-40% dropwise to the reactor. After the addition is complete, heat the reaction system to 85-90℃ and stir at a constant temperature for 2-4 hours to induce a condensation reaction. After the reaction is complete, discharge the material and cool it to room temperature to finally obtain the aliphatic water-reducing agent.

[0018] Furthermore, the modified water-reducing agent is prepared by the following steps:

[0019] After mixing the aliphatic water-reducing agent, hydroxypropyl methylcellulose and retarder according to the weight parts, stir and mix at a speed of 60-80 r / min for 20-30 min. After the mixing is completed, the modified water-reducing agent is obtained.

[0020] Furthermore, the hydroxypropyl methylcellulose is of type HD6100; the retarder is citric acid.

[0021] Furthermore, the composite fiber is composed of modified PVA fiber and steel fiber. The PVA fiber has a length of 9-12 mm, a single filament diameter of 15-30 μm, and a tensile strength ≥1000 MPa; the steel fiber has a length of 10-13 mm, a diameter of 0.2-0.3 mm, and a tensile strength ≥2000 MPa.

[0022] Furthermore, the preparation steps of the modified PVA fiber are as follows:

[0023] Step B1: Immerse the PVA fibers in a sodium hydroxide solution with a mass fraction of 0.5% to 1.0% for a light surface activation treatment for 3 to 6 minutes, then wash with deionized water until neutral and dry.

[0024] Step B2: Mix silane coupling agent KH-550 with 95% ethanol at a mass ratio of 1:45-55, pre-hydrolyze for 20-40 min to obtain KH-550 hydrolysate; add the slightly activated PVA fiber obtained in step B1 to the KH-550 hydrolysate, treat at 25-40℃ for 20-60 min, remove and dry to obtain KH-550 base-coated PVA fiber;

[0025] Step B3: Disperse hydrophobic nano-silica with an average particle size of 10-50 nm in a 95% ethanol solution and ultrasonically disperse for 10-30 min to obtain a hydrophobic nano-silica dispersion; add the KH-550 primer PVA fiber obtained in step B2 to the hydrophobic nano-silica dispersion and treat for 10-30 min to load the hydrophobic nano-silica onto the surface of the PVA fiber;

[0026] Step B4: Remove the fiber and dry it at 40-60℃ to obtain modified PVA fiber.

[0027] As a further aspect of the present invention, the present invention also provides a method for preparing ultra-high performance geopolymer concrete suitable for rapid repair of heavy-haul railway tracks and bridges, comprising the following steps:

[0028] Step S1: Weigh each raw material according to the weight parts, put the slag powder, silica fume and medium sand into the cement mortar mixer and mix at 50-70 r / min for 2-5 minutes to make it fully mixed and obtain the mixed dry material;

[0029] Step S2: Add alkali activator solution and water to the above mixed dry material, stir at 110-130 r / min for 1-2 min, then add modified water-reducing agent, stir at 110-130 r / min for 1-2 min, then add composite fiber, stir at 110-130 r / min for 2-5 min, and after completion, a mixture is obtained.

[0030] Step S3: After the mixture is poured into shape, it is cured at a temperature of 20±2℃ and a curing humidity of ≥90% until the predetermined age is obtained, thus obtaining the ultra-high performance geopolymer concrete suitable for rapid repair of heavy-load railway tracks and bridges.

[0031] The beneficial effects of this invention are:

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. This invention uses slag powder and silica fume as the main cementing materials, and forms a geopolymer cementing system through alkali activation, reducing the amount of cement clinker used, realizing the resource utilization of industrial by-products, and has green, low-carbon and secondary utilization value.

[0034] 2. This invention uses modified PVA fiber and steel fiber to form a composite fiber reinforcement system. The modified PVA fiber avoids premature debonding due to weak interface and reduces the probability of premature breakage of PVA fiber due to excessive chemical bonding. The PVA fiber mainly plays the role of microcrack bridging, slippage and pull-out energy dissipation, while the steel fiber mainly plays the role of macrocrack bridging and load bearing. The two work together to improve the flexural strength, crack resistance and toughness of the material.

[0035] 3. This invention uses an aliphatic water-reducing agent, hydroxypropyl methylcellulose and citric acid to form a modified water-reducing agent, which can improve the fluidity retention, water retention and setting time of the high-alkali polymer system, reduce the risk of composite fiber agglomeration and improve the construction applicability of the material.

[0036] 4. The material of this invention has high early strength, interfacial bonding strength and low drying shrinkage rate, and is suitable for rapid repair of heavy-load railway tracks and bridges. It can reduce the risk of cracking of the repair layer and secondary damage, and extend the service life of existing track and bridge structures. Detailed Implementation

[0037] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Furthermore, unless otherwise specified, the raw materials, reagents, or devices used in the following embodiments can be obtained from conventional commercial channels or by existing known methods.

[0038] Unless otherwise specified, the slag powder used in the following examples and comparative examples is S95 grade blast furnace slag powder with a specific surface area of ​​420-450 m² / kg, a density of 2.8-3.0 g / cm³, a CaO content of 38%-42%, and a SiO₂ content of 32%-36%; the silica fume used has a SiO₂ content ≥92%, an average particle size of 0.1-0.5 μm, a specific surface area of ​​18000-22000 m² / kg, and a water requirement ratio ≤105%; the medium sand used is sieved natural river sand with a fineness modulus of 2.6-2.8, a mud content <1.0%, a clay lump content <0.5%, and a moisture content <0.1%.

[0039] Preparation Example 1: Preparation of Alkali Activator Solution

[0040] Sodium hydroxide was added to 50 mL of pure water in three batches with stirring. The mixture was stirred at 400 rpm until the sodium hydroxide was completely dissolved, and then allowed to stand and cool to 25 °C. Liquid sodium silicate with a modulus of 3.32 and a solid content of 39.99% was then added to the solution. The mixture was stirred at 400 rpm for 20–30 min until the solution was transparent and homogeneous. After stirring, the solution was allowed to stand at room temperature for 24 h to obtain the alkali activator solution.

[0041] Preparation Example 2: Preparation of Aliphatic Water-Reducing Agents

[0042] Step A1: Add 200mL of pure water to the reactor, then add 8.0-10.0g of sodium sulfite while stirring. Heat the reactor to 55℃ and stir at a constant temperature until the solid components are completely dissolved.

[0043] Step A2: Add 20.0-22.0g of cyclohexanone to the reactor and continue sulfonation at a constant temperature of 50℃ for 50-60 minutes.

[0044] Step A3: After sulfonation is complete, add 100 mL of 37% formaldehyde solution dropwise to the reactor. After the addition is complete, heat the reaction system to 85-90°C and stir at a constant temperature for 2-4 hours to induce a condensation reaction. After the reaction is complete, discharge the material and cool it to room temperature to obtain an aliphatic water-reducing agent.

[0045] Preparation Example 3: Preparation of Modified PVA Fibers

[0046] Step B1: Immerse the PVA fibers in a sodium hydroxide solution with a mass fraction of 0.5% to 1.0% for a light surface activation treatment for 3 to 6 minutes, then wash with deionized water until neutral and dry.

[0047] Step B2: Mix silane coupling agent KH-550 with 95% ethanol at a mass ratio of 1:50, pre-hydrolyze for 20-40 min to obtain KH-550 hydrolysate; add the slightly activated PVA fiber obtained in step B1 to the KH-550 hydrolysate, treat at 25-40℃ for 20-60 min, remove and dry to obtain KH-550 base-coated PVA fiber;

[0048] Step B3: Disperse hydrophobic nano-silica with an average particle size of 10-50 nm in a 95% ethanol solution and ultrasonically disperse for 10-30 min to obtain a hydrophobic nano-silica dispersion; add the KH-550 primer PVA fiber obtained in step B2 to the hydrophobic nano-silica dispersion and treat for 10-30 min to load the hydrophobic nano-silica onto the surface of the PVA fiber;

[0049] Step B4: Remove the fiber and dry it at 40-60℃ to obtain modified PVA fiber.

[0050] Example 1

[0051] An ultra-high performance geopolymer concrete suitable for rapid repair of heavy-load railway tracks and bridges is composed of the following raw materials by weight: 1 part slag powder; 0.26 parts silica fume; 1.05 parts medium sand; 0.28 parts alkali activator solution; 0.012 parts modified water-reducing agent; 0.10 parts water; and composite fibers added by volume, of which 0.3% are modified PVA fibers, 1.2% are steel fibers, and the total volume of composite fibers is 1.5%.

[0052] In this embodiment, when preparing the alkaline activator solution, the amount of sodium hydroxide added is 20g and the amount of liquid sodium silicate added is 150g.

[0053] In this embodiment, the modified water-reducing agent is prepared by mixing an aliphatic water-reducing agent, hydroxypropyl methylcellulose and citric acid, wherein the aliphatic water-reducing agent is 25 parts, the hydroxypropyl methylcellulose is 2 parts and the citric acid is 4 parts; the above components are stirred and mixed at 60 r / min for 20 min to obtain the modified water-reducing agent.

[0054] In this embodiment, the composite fiber is composed of modified PVA fiber and steel fiber. The PVA fiber has a length of 9 mm, a single filament diameter of 20 μm, and a tensile strength ≥1000 MPa; the steel fiber has a length of 10 mm, a diameter of 0.22 mm, and a tensile strength ≥2000 MPa. The modified PVA fiber and steel fiber are weighed after being converted to mass according to volume content, and then premixed to form the composite fiber.

[0055] In this embodiment, the preparation conditions of the modified PVA fiber are as follows: the PVA fiber is treated with 0.5% sodium hydroxide solution for 3 min and washed until neutral; the amount of KH-550 is 0.3% of the mass of the PVA fiber, KH-550 is mixed with 95% ethanol at a mass ratio of 1:50, pre-hydrolyzed for 20 min, and the PVA fiber is treated at 25°C for 20 min; the amount of hydrophobic nano-silica is 0.2% of the mass of the PVA fiber, ultrasonically dispersed for 10 min and then treated for 10 min, and then dried at 40°C for 1 h to obtain the modified PVA fiber.

[0056] The preparation method of this embodiment includes the following steps:

[0057] Step S1: Weigh each raw material according to the weight parts, put the slag powder, silica fume and medium sand into the cement mortar mixer and mix at 60 r / min for 3 minutes to make it fully mixed and obtain the mixed dry material;

[0058] Step S2: Add the prepared alkali activator solution and water to the above mixed dry material, stir at 120 r / min for 1 min, then add the modified water-reducing agent prepared in this embodiment, stir at 120 r / min for 1 min, then add the prepared composite fiber, stir at 120 r / min for 3 min, and after completion, a mixture is obtained.

[0059] Step S3: After the mixture is poured into shape, it is cured at a temperature of 20±2℃ and a curing humidity of ≥90% until the predetermined age is obtained, thus obtaining ultra-high performance geopolymer concrete suitable for rapid repair of heavy-load railway tracks and bridges.

[0060] Example 2

[0061] An ultra-high performance geopolymer concrete suitable for rapid repair of heavy-load railway tracks and bridges is composed of the following raw materials by weight: 1 part slag powder; 0.30 parts silica fume; 1.15 parts medium sand; 0.32 parts alkali activator solution; 0.020 parts modified water-reducing agent; 0.08 parts water; and composite fibers added by volume, of which 0.4% are modified PVA fibers, 1.4% are steel fibers, and the total volume content of composite fibers is 1.8%.

[0062] In this embodiment, when preparing the alkaline activator solution, the amount of sodium hydroxide added is 25g, and the amount of liquid sodium silicate added is 155g.

[0063] In this embodiment, the modified water-reducing agent is prepared by mixing an aliphatic water-reducing agent, hydroxypropyl methylcellulose and citric acid, wherein the aliphatic water-reducing agent is 28 parts, the hydroxypropyl methylcellulose is 3 parts and the citric acid is 5 parts; the above components are stirred and mixed at 80 r / min for 30 min to obtain the modified water-reducing agent.

[0064] In this embodiment, the composite fiber is composed of modified PVA fiber and steel fiber. The PVA fiber has a length of 12 mm, a single filament diameter of 20 μm, and a tensile strength ≥1000 MPa; the steel fiber has a length of 10 mm, a diameter of 0.22 mm, and a tensile strength ≥2000 MPa.

[0065] In this embodiment, the preparation conditions of the modified PVA fiber are as follows: the PVA fiber is treated with 0.8% sodium hydroxide solution for 5 min and washed until neutral; the amount of KH-550 is 0.6% of the mass of the PVA fiber; KH-550 and 95% ethanol are mixed at a mass ratio of 1:50; pre-hydrolyzed for 30 min; the PVA fiber is treated at 35°C for 40 min; the amount of hydrophobic nano-silica is 0.8% of the mass of the PVA fiber; after ultrasonic dispersion for 20 min, it is treated for 20 min; and then dried at 50°C for 1.5 h to obtain the modified PVA fiber.

[0066] The preparation method of this embodiment is the same as that of Example 1, except that in step S2, after the alkali activator solution is added, it is stirred for 2 minutes, and after the modified water-reducing agent and medium sand are added, it is stirred for 2 minutes.

[0067] Example 3

[0068] An ultra-high performance geopolymer concrete suitable for rapid repair of heavy-load railway tracks and bridges, composed of the following raw materials by weight:

[0069] 1 part slag powder; 0.34 parts silica fume; 1.25 parts medium sand; 0.38 parts alkali activator solution; 0.030 parts modified water-reducing agent; 0.08 parts water; composite fiber is added according to volume ratio, of which 0.5% is modified PVA fiber, 1.5% is steel fiber, and the total volume ratio of composite fiber is 2.0%.

[0070] In this embodiment, when preparing the alkaline activator solution, the amount of sodium hydroxide added is 30g and the amount of liquid sodium silicate added is 160g.

[0071] In this embodiment, the modified water-reducing agent is prepared by mixing an aliphatic water-reducing agent, hydroxypropyl methylcellulose and citric acid, wherein the aliphatic water-reducing agent is 30 parts, the hydroxypropyl methylcellulose is 3 parts and the citric acid is 5 parts; the above components are stirred and mixed at 80 r / min for 30 min to obtain the modified water-reducing agent.

[0072] In this embodiment, the composite fiber is composed of modified PVA fiber and steel fiber. The PVA fiber has a length of 12 mm, a single filament diameter of 20 μm, and a tensile strength ≥1000 MPa; the steel fiber has a length of 13 mm, a diameter of 0.25 mm, and a tensile strength ≥2000 MPa.

[0073] In this embodiment, PVA fibers were treated with 1.0% sodium hydroxide solution for 6 min and washed until neutral. The amount of KH-550 was 1.0% of the mass of PVA fibers. KH-550 was mixed with 95% ethanol at a mass ratio of 1:50 and pre-hydrolyzed for 40 min. The PVA fibers were then treated at 40°C for 60 min. The amount of hydrophobic nano-silica was 1.5% of the mass of PVA fibers. After ultrasonic dispersion for 30 min, the fibers were treated for another 30 min and then dried at 60°C for 2 h to obtain modified PVA fibers.

[0074] The preparation method of this embodiment is the same as that of Example 1, except that in step S2, after the alkali activator solution is added, it is stirred for 2 minutes, and after the modified water-reducing agent and medium sand are added, it is stirred for 2 minutes.

[0075] Comparative Example 1

[0076] This comparative example serves as the control group for Example 2. The only difference from Example 2 is that the composite fibers in Example 2 are replaced with an equal amount of modified PVA fibers; the remaining raw material composition, raw material amounts, and preparation steps are the same as in Example 2.

[0077] Comparative Example 2

[0078] This comparative example serves as the control group for Example 2. The only difference from Example 2 is that the composite fibers in Example 2 are replaced with an equal amount of single steel fibers; the remaining raw material composition, raw material amounts, and preparation steps are the same as in Example 2.

[0079] Comparative Example 3

[0080] This comparative example serves as the control group for Example 2. The only difference from Example 2 is that the modified water-reducing agent in Example 2 is replaced with an equal amount of commercially available polycarboxylate water-reducing agent; the remaining raw material composition, raw material amounts, and preparation steps are the same as in Example 2.

[0081] Comparative Example 4

[0082] The interface-controlled PVA fiber in Example 2 was replaced with ordinary PVA fiber without surface treatment. The volume content of PVA fiber remained at 0.4%, the volume content of steel fiber remained at 1.4%, and the other conditions remained the same.

[0083] Comparative Example 5

[0084] This comparative example serves as the control group for Example 2. The only difference from Example 2 is that the hydrophobic nano-silica in Example 2 is replaced with an equal amount of ordinary hydrophilic nano-silica. All other aspects, including mild NaOH surface activation, KH-550 primer application, raw material composition, fiber volume fraction, water-reducing agent composition, curing regime, and preparation steps, are the same as in Example 2.

[0085] Comparative Example 6

[0086] This comparative example serves as the control group for Example 2. The only difference from Example 2 is that the modified water-reducing agent in Example 2 is replaced with an equal amount of aliphatic water-reducing agent, which was prepared using Preparation Example 2; hydroxypropyl methylcellulose and citric acid are not added. All other raw material compositions, amounts, and preparation steps are the same as in Example 2.

[0087] Test Example 1

[0088] To evaluate the construction performance, early mechanical properties, long-term mechanical properties, interfacial bonding performance and volume stability of the ultra-high performance geopolymer concrete of the present invention, the mixtures prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were subjected to performance tests.

[0089] Each mixture was cast into a mold and cured at 20±2℃ and relative humidity ≥90% for the corresponding test age before testing. The test ages included 4h, 12h, and 28d, where 4h and 12h were used to evaluate the early mechanical properties of the material, and 28d was used to evaluate the long-term mechanical properties, interfacial adhesion properties, and drying shrinkage properties of the material.

[0090] The specimen molding, curing, and basic mechanical property tests such as compressive strength and flexural strength were conducted in accordance with the "Basic Properties and Test Methods of Ultra-High Performance Concrete" (T / CBMF 37-2018 / T / CCPA 7-2018). The initial setting time was determined according to the setting time test method in the "Standard for Test Methods of Performance of Ordinary Concrete Mixtures" (GB / T 50080-2016). The spread was determined using the vibration-free truncated cone mold spread method: the initial spread was measured within 2 minutes after mixing; the 30-minute spread was measured after the mixture was sealed and allowed to stand for 30 minutes, followed by low-speed mixing for 30 seconds, and then measured using the above method.

[0091] The 28-day oblique shear bond strength was tested using oblique shear specimens. C50 concrete substrate specimens were used, with the bonding surface roughened and cleaned. The material of this invention was then poured onto the bonding surface of the substrate specimen to form a composite oblique shear specimen of old and new concrete. Compressive and shear loading was applied, and the failure load was recorded. The 28-day drying shrinkage rate was tested according to the "Standard for Test Methods of Long-Term Performance and Durability of Concrete".

[0092] The results of each test are shown in Table 1.

[0093]

[0094] It should be noted that, in this document, terms such as “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus.

[0095] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A high-performance geopolymer concrete suitable for rapid repair of heavy-load railway tracks and bridges, characterized in that, The ultra-high performance geopolymer concrete comprises a matrix material and composite fibers; the matrix material, based on slag powder as 1 part by weight, consists of the following raw materials in parts by weight: 1 part slag powder; 0.26-0.34 parts silica fume; 1.05-1.25 parts medium sand; 0.28-0.38 parts alkali activator solution; 0.012-0.030 parts modified water-reducing agent; and 0.06-0.10 parts water; the modified water-reducing agent is a compound of aliphatic water-reducing agent, hydroxypropyl methylcellulose, and citric acid; The composite fiber is composed of modified PVA fiber and steel fiber. The PVA fiber has a length of 9-12 mm, a single filament diameter of 15-30 μm, and a tensile strength ≥1000 MPa; the steel fiber has a length of 10-13 mm, a diameter of 0.2-0.3 mm, and a tensile strength ≥2000 MPa. The preparation steps of the modified PVA fiber are as follows: Step B1: Immerse the PVA fibers in a sodium hydroxide solution with a mass fraction of 0.5% to 1.0% for a light surface activation treatment for 3 to 6 minutes, then wash with deionized water until neutral and dry. Step B2: Mix silane coupling agent KH-550 with 95% ethanol at a mass ratio of 1:45-55, pre-hydrolyze for 20-40 min to obtain KH-550 hydrolysate; add the slightly activated PVA fiber obtained in step B1 to the KH-550 hydrolysate, treat at 25-40℃ for 20-60 min, remove and dry to obtain KH-550 base-coated PVA fiber; Step B3: Disperse hydrophobic nano-silica with an average particle size of 10-50 nm in a 95% ethanol solution and ultrasonically disperse for 10-30 min to obtain a hydrophobic nano-silica dispersion; add the KH-550 primer PVA fiber obtained in step B2 to the hydrophobic nano-silica dispersion and treat for 10-30 min to load the hydrophobic nano-silica onto the surface of the PVA fiber; Step B4: Remove the fiber and dry it at 40-60℃ to obtain modified PVA fiber; Based on the total volume of the ultra-high performance geopolymer concrete mixture, the total volume content of the composite fiber is 1.5% to 2.0%; wherein, the volume content of the modified PVA fiber is 0.3% to 0.5%, the volume content of the steel fiber is 1.2% to 1.5%, and the modified PVA fiber is PVA fiber that has been surface activated and then treated with silane coupling agent KH-550 and hydrophobic nano silica.

2. The ultra-high performance geopolymer concrete suitable for rapid repair of heavy-haul railway tracks and bridges according to claim 1, characterized in that, The blast furnace slag powder is S95 grade blast furnace slag powder with a specific surface area of ​​420-450 m². 2 / kg, density is 2.8~3.0g / cm³ 3 The CaO content is 38%–42%, and the SiO2 content is 32%–36%.

3. The ultra-high performance geopolymer concrete suitable for rapid repair of heavy-haul railway tracks and bridges according to claim 1, characterized in that, The silica fume has a SiO2 content of ≥92%, an average particle size of 0.1–0.5 μm, and a specific surface area of ​​18,000–22,000 m². 2 / kg, water requirement ratio ≤105%.

4. The ultra-high performance geopolymer concrete suitable for rapid repair of heavy-haul railway tracks and bridges according to claim 1, characterized in that, Medium sand is natural river sand that has been screened, with a fineness modulus of 2.6 to 2.8, a mud content of <1.0%, a mud lump content of <0.5%, and a moisture content of <0.1%.

5. The ultra-high performance geopolymer concrete suitable for rapid repair of heavy-haul railway tracks and bridges according to claim 1, characterized in that, The alkali activator solution is prepared by the following steps: 20-30g of sodium hydroxide is added to 50mL of pure water in three batches with stirring. After stirring at 400r / min until the sodium hydroxide is completely dissolved, the solution is allowed to stand and cool to 25℃. Then, 150-160g of liquid sodium silicate with a modulus of 3.32 and a solid content of 39.99% is added to the solution. The solution is stirred at 400r / min for 20-30min until it becomes transparent and homogeneous. After the solution is completed, it is allowed to stand at room temperature for 24h to obtain the alkali activator solution.

6. The ultra-high performance geopolymer concrete suitable for rapid repair of heavy-haul railway tracks and bridges according to claim 1, characterized in that, The modified water-reducing agent comprises the following raw materials in parts by weight: aliphatic water-reducing agent: 25-30 parts; hydroxypropyl methylcellulose: 2-3 parts; citric acid as a retarder: 4-5 parts; the modified water-reducing agent is prepared by the following steps: Step A1: Add 200mL of pure water to the reactor, then add 8.0-10.0g of sodium sulfite (AR grade, 97% purity) to the pure water while stirring. Heat the reactor to 50-60℃ and stir at a constant temperature until the solid components are completely dissolved. Step A2: Add 20.0-22.0g of cyclohexanone (AR grade, 99.5% purity) to the reactor and continue stirring and sulfonating at 45-55℃ for 50-60 minutes. Step A3: After sulfonation is complete, add 90-110 mL of formaldehyde solution with a mass fraction of 35-40% dropwise to the reactor. After the addition is complete, heat the reaction system to 85-90℃ and stir at a constant temperature for 2-4 hours to carry out the condensation reaction. After the reaction is complete, discharge the material and cool it to room temperature to finally obtain the aliphatic water-reducing agent. Step A4: After mixing the aliphatic water-reducing agent, hydroxypropyl methylcellulose and retarder weighed by weight, stir and mix at a speed of 60-80 r / min for 20-30 min. After the mixture is mixed, the modified water-reducing agent is obtained.

7. The ultra-high performance geopolymer concrete suitable for rapid repair of heavy-haul railway tracks and bridges according to claim 1, characterized in that, Based on the mass of PVA fibers, the amount of the silane coupling agent KH-550 is 0.3% to 1.2%, preferably 0.5% to 1.0%; the amount of the hydrophobic nano-silica is 0.2% to 1.5%.

8. A method for preparing ultra-high performance geopolymer concrete suitable for rapid repair of heavy-haul railway tracks and bridges according to any one of claims 1 to 7, characterized in that, Includes the following steps: Step S1: Weigh each raw material according to the weight parts, put the slag powder, silica fume and medium sand into the cement mortar mixer and mix at 50-70 r / min for 2-5 minutes to make it fully mixed and obtain the mixed dry material; Step S2: Add alkali activator solution and water to the above mixed dry material, stir at 110-130 r / min for 1-2 min, then add modified water-reducing agent, stir at 110-130 r / min for 1-2 min, then add composite fiber, stir at 110-130 r / min for 2-5 min, and after completion, a mixture is obtained. Step S3: After the mixture is poured into shape, it is cured at a temperature of 20±2℃ and a curing humidity of ≥90% until the predetermined age is obtained, thus obtaining the ultra-high performance geopolymer concrete suitable for rapid repair of heavy-load railway tracks and bridges.

Citation Information

Patent Citations

  • A high-temperature resistant, high-ductility fiber-reinforced cementitious composite material and its preparation method

    CN106380147B

  • Nanometer SiO2 and PVA (polyvinyl alcohol) fiber reinforced geopolymer mortar

    CN108892424A